2011
DOI: 10.1103/physrevb.84.104421
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced ultrafast spin dynamics in ErFeO3

Abstract: Using 100-fs optical laser pulses, we have been able to excite and probe spin dynamics in the rare-earth orthoferrite ErFeO 3 . The investigation was performed in a broad temperature range with the focus on the vicinities of the compensation point T comp ≈ 47 K and the spin reorientation transition region in the interval 86 K T 99 K. Spin precession excited by the laser pulse was present in a large part of the investigated temperature range, but was especially strong near the spin reorientation region. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 162 publications
(87 citation statements)
references
References 31 publications
(49 reference statements)
2
84
0
1
Order By: Relevance
“…Following excitation by femtosecond optical pulses with a peak fluence of ∼10 mJ/cm 2 and focused to spot of ß1 mm radius, TmFeO 3 and ErFeO 3 demonstrate ultrafast spin-reorientation dynamics, which we resolve by monitoring THz emission signals. We show that the THz emission spectroscopy serves as an alternative and complementary tool with respect to the more conventional all-optical pump-probe spectroscopy applied to study these materials previously [10][11][12]. Moreover, the power of this technique is evidenced here by the observation of an as yet unobserved optical excitation of dipole active modes in the vicinity of the spin-reorientation phase transition.…”
Section: Experiments and Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Following excitation by femtosecond optical pulses with a peak fluence of ∼10 mJ/cm 2 and focused to spot of ß1 mm radius, TmFeO 3 and ErFeO 3 demonstrate ultrafast spin-reorientation dynamics, which we resolve by monitoring THz emission signals. We show that the THz emission spectroscopy serves as an alternative and complementary tool with respect to the more conventional all-optical pump-probe spectroscopy applied to study these materials previously [10][11][12]. Moreover, the power of this technique is evidenced here by the observation of an as yet unobserved optical excitation of dipole active modes in the vicinity of the spin-reorientation phase transition.…”
Section: Experiments and Resultsmentioning
confidence: 81%
“…The spectral component at 0.1 THz, which we assign to the quasi-ferromagnetic mode of the iron sublattices, is excited in the relatively narrow temperature interval between 50 and 70 K. It is natural to assume that this mode is excited just below the spin-reorientation temperature range, as was observed in optical experiments [10][11][12]. The shift of ß20 K from the spin-reorientation region (80-90 K) is due to the steady-state temperature buildup via cumulative laser heating.…”
Section: Experiments and Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The few studies done show a maximum 20 • reorientation. 35,[43][44][45] It seems that ultrafast laser heating is not equivalent to slow heating. Such an effect has been reported in another system has well, 46 where it was suggested that the laser pulse brings the system into a metastable state not accessible otherwise.…”
Section: B Transient Statementioning
confidence: 99%